Presence of MDSC associates with impaired antigen-specific T cell reactivity following COVID-19 vaccination in cirrhotic patients - Törnell, Andreas; Blick, Elin; Al-Dury, Samer; Grauers Wiktorin, Hanna; Waern, Johan; Ringlander, Johan; Einarsdottir, Sigrun; Lindh, Magnus; Hellstrand, Kristoffer; Lagging, Martin; Martner, Anna (Frontiers in Immunology, 2023)
Background & Aims: Cirrhosis entails high risk of serious infections and abated efficiency of vaccination, but the underlying mechanisms are only partially understood. This study aimed at characterizing innate and adaptive immune functions, including antigen-specific T cell responses to COVID-19 vaccination, in patients with compensated and decompensated cirrhosis. Methods: Immune phenotype and function in peripheral blood from 42 cirrhotic patients and 44 age-matched healthy controls were analysed after two doses of the mRNA-based COVID-19 vaccines (BNT162b2 (Pfizer BioNTech) or mRNA-1273 (Moderna)). Results: Cirrhotic patients showed significantly reduced blood counts of antigen-presenting dendritic cells (DC) and high counts of monocytic myeloid-derived suppressor cells (M-MDSC) as compared to healthy controls. In addition, monocytic cells recovered from cirrhotic patients showed impaired expression of the antigen-presenting molecule HLA-DR and the co-stimulatory molecule CD86 upon Toll-like receptor (TLR) stimulation. These features were more prominent in patients with decompensated cirrhosis (Child-Pugh classes B & C). Interestingly, while patients with compensated cirrhosis (Child-Pugh class A) showed an inflammatory profile with myeloid cells producing the proinflammatory cytokines IL-6 and TNF, decompensated patients produced reduced levels of these cytokines. Cirrhotic patients, in particular those with more advanced end-stage liver disease, mounted reduced antigen-specific T cell reactivity to COVID-19 vaccination. Vaccine efficiency inversely correlated with levels of M-MDSC. Conclusions: These results implicate MDSC as mediators of immunosuppression, with ensuing deficiency of vaccine-specific T cell responses, in cirrhosis.